‘Like a Japanese Christmas Card’: Line in Poetry and Art - Ross J (University of Canberra: Centre for Creative & Cultural Research)
A line can be seen in two ways: as a break or a harmony. In poetry, this manifests as the contrast between a stop and an invitation to continuance: a heroic couplet or the enjambments of blank verse. A series of analogies are made here between the aural and visual arts – from sources such as a 1998 interview with New Zealand poet Graham Lindsay, William Hogarth’s 1753 treatise The Analysis of Beauty, and Louise Bourgeois’s ‘Arch of Hysteria’ (1993), as well as my own novel Nights with Giordano Bruno (2000) – to understand better the implications of these two ways of characterising a line. On the one hand, there is the static predictability of a safe tradition, on the other, the danger of the ‘flame of fire’ which Hogarth maintains to be the best way to imagine his own serpentine ‘line of beauty.’ While both aspects are undoubtedly necessary, it is argued that the preference must always be given – for all its dangers and the certainty of pain it brings with us – to (in Freudian terms) the Pleasure Principle over the obsessive-compulsive stasis of his Death Principle.
Keywords: Louise Bourgeois; William Hogarth; Graham Lindsay; Guillaume Apollinaire; Sigmund Freud; 1901 Art Theory and Criticism; 1904 Performing Arts and Creative Writing